INTERPRETATION OF FAJR ṢĀDIQ AND FAJR KĀDHIB IN Al-SHĀFI’Ī SCHOOL’S TEXTS: A HADITH AND ASTRONOMICAL PERSPECTIVES - Qulub, Siti Tatmainul; Nadhifah, Nurul Asiya; Ahmad Munif; Mokhamad Ali Ridlo (Al-Hilal: Journal of Islamic Astronomy, 2024)
This study explores the interpretation of false dawn (fajr kādhib) and true dawn (fajr ṣādiq) in al-Shāfi’ī fiqh texts through the lenses of hadith and astronomy. It compares classical definitions by al-Rāfi'ī and al-Nawawī with contemporary scientific and hadith-based perspectives. Using documentation and descriptive-critical analysis, the research finds that fajr kādhib is described as vertical light (mustathil) resembling a wolf's tail, appearing briefly and vanishing. In contrast, fajr ṣādiq is horizontal light (mustaṭīr) spreading across the horizon, gradually brightening. From a hadith perspective, this aligns with al-mu'taridh (true dawn) and al-mustathil (false dawn). Astronomically, fajr kādhib matches zodiacal light, which doesn’t disappear, and fajr ṣādiq corresponds to sunlight scattering. Thus, the disappearance of fajr kādhib, as described in classical texts, lacks modern scientific support.